The external contingencies and development processes of students with emotional disabilities - Nikolaros, John (Faculty of Education, University of the Free State, 2015)
This paper examines the external contingencies that students with emotional disabilities (ED) experience throughout childhood and adolescence. It presents an in-depth assessment of the impact of external dynamics on the emotional development of students with ED, and considers the school, home, and community support systems. The paper assesses school implementation and the ability to influence the regulation process, along with a review of strategy that assists schools and parents in assessing interventions.
Keywords: Emotional disabilities; Psychopathology; Emotional intelligence(IE); Behaviours